Meat Power in a Tropical Region of Mexico: Unequal Power Relations and Vulnerabilities Between the Transnational Beef Industry and Small- and Medium-Scale Cattle Raisers - Lazos-Chavero, Elena (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
Conventional extensive cattle raising has involved deforestation and biodiversity loss in tropical regions throughout the world. In Mexico, since the 1990s, cattle raising has largely undergone economic and political transformation from free-range grazing to feedlots owned by large transnational meat corporations, along with increased meat exportation. Transnational corporations exercise power over small- and medium-scale cattle raisers by setting prices and conditions upon purchasing their young cattle to complete their development in feedlots, leading to vulnerabilities and inequalities based on the scale of production. Low prices paid to cattle raisers result in a lack of investment in innovations and sustainable practices, while middlemen and feedlots earn very high profits. The corporations further increase their meat power by shortening the fattening period of the cattle and exercising control over the entire cattle production process. This article analyzes how the current cattle-raising model, which favors large feedlots, has led to vulnerabilities for small- and medium-scale cattle raisers of southern Veracruz, Mexico, as well as the economic, social, political, and cultural obstacles to sustainable forms of cattle raising as a result of the imposition of this model. Silvopastoral systems have been implemented to raise livestock while also recovering rainforests and water security in the study region. However, the fact that these cattle are sold to feedlots for their final stage of development limits the implementation of sustainable cattle raising systems. As a result of extensive fieldwork in the Los Tuxtlas region involving interviews, focal groups, and workshops, scholars (including the author), cattle raisers, and NGOs have been jointly developing and implementing a sustainable cattle-raising project based on silvopastoral systems since 2019.